Uniquely identifying the variable order of time-fractional partial differential equations on general multi-dimensional domains. Issue 10 (3rd October 2021) - Zheng, Xiangcheng; Wang, Hong
ABSTRACT: We proved the unique determination of the variable order in a two-scale mobile–immobile variable-order time-fractional partial differential equation with a variable diffusivity tensor imposed on a general multi-dimensional domain, with the observations of the unknown solutions on any arbitrarily small spatial domain over a sufficiently small time interval. The proved theorem provides a guidance where the measurements should be performed and ensures that with these observations the uniqueness of the identification is theoretically guaranteed.